Renewable Energy in Wilderness Landscapes: Visitors’ Perspectives - Edita Tverijonaite; Anna Dóra Sæþórsdóttir; Rannveig Ólafsdóttir; C. Michael Hall (Sustainability, 2019)
Increasing the share of renewable energy in the energy mix is of crucial importance for climate change mitigation. However, as renewable energy development often changes the visual appearance of landscapes and might affect other industries relying on them, such as nature-based tourism, it therefore requires careful planning. This is especially true in Iceland, a country rich in renewable energy resources and a popular nature-based tourism destination. The present study investigated the potential impacts on tourism of the proposed Hverfisfljót hydropower plant by identifying the main attractions of the area as well as by analyzing visitors’ perceptions, preferences and attitudes, and the place meanings they assign to the landscape of the area. The data for the study were collected using onsite questionnaire surveys, interviews with visitors to the area, open-ended diaries, and participant observation. The results reveal that the area of the proposed power plant is perceived as wilderness by its visitors, who seek environmental settings related to the components of a wilderness experience. Visitors were highly satisfied with the present settings and preferred to protect the area from development to ensure the provision of currently available recreational opportunities. The results further show that the proposed Hverfisfljót hydropower plant would reduce the attractiveness of the area to its visitors, degrade their wilderness experience, and therefore strongly reduce their interest in visiting the area. Moreover, the participants perceived the already developed lowlands of the country as more suitable for renewable energy development than the undeveloped highland areas, which is in line with the principles of smart practices for renewable energy development.